2018
DOI: 10.1021/acs.analchem.7b05225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Phenomena of Atomic Force Microscopy Scanning

Abstract: Atomic force microscopy is widely used for nanoscale characterization of materials by scientists worldwide. The long-held belief of ambient AFM is that the tip is generally chemically inert but can be functionalized with respect to the studied sample. This implies that basic imaging and scanning procedures do not affect surface and bulk chemistry of the studied sample. However, an in-depth study of the confined chemical processes taking place at the tip−surface junction and the associated chemical changes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The chemical sensitivity of SIMS allows the detection of the ion distribution on the surface of the sample with a spatial resolution of ~120 nm. [47,48] Figure 5a demonstrates an averaged mass spectrum with all the base elements Bi + , Fe + , and Li + present. The distribution of the corresponding peak area as a function of spatial location allows characterization of local chemical changes in the studied area.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical sensitivity of SIMS allows the detection of the ion distribution on the surface of the sample with a spatial resolution of ~120 nm. [47,48] Figure 5a demonstrates an averaged mass spectrum with all the base elements Bi + , Fe + , and Li + present. The distribution of the corresponding peak area as a function of spatial location allows characterization of local chemical changes in the studied area.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Si + is due to the surface contamination by silicone oils, which originates from the poly-dimethyl siloxane (PDMS) gel boxes, used for tips storage. [28][29] This contamination affected only a thin top layer of material (~1 nm), which is excluded from data analysis. Si concentration was found to be independent of domain polarity, and hence is not expected to affect the domain-specific phenomena.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…During piezoresponse force microscopy (PFM) switching studies, the application of a high bias to the tip not only leads to polarization reversal, but also to significant electrochemical effects at the surface. 41 These include the deposition, injection or removal of surface charges, 6,42 as well as structural and chemical changes 43 such as the ordering of vacancies, or even significant surface and sub-surface damage of the sample. 28,41 While many of the electrostatic changes appear to be at least partially reversible, as shown by electrostatic force microscopy (EFM) and Kelvin probe force microscopy (KPFM) measurements of surface charge screening written domains, 6,9,10,22 the chemical effects are not, and obviously influence in their turn the physical properties of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…28,41 While many of the electrostatic changes appear to be at least partially reversible, as shown by electrostatic force microscopy (EFM) and Kelvin probe force microscopy (KPFM) measurements of surface charge screening written domains, 6,9,10,22 the chemical effects are not, and obviously influence in their turn the physical properties of the sample. Recent studies have shown that even the simple act of contact scanning with an unbiased tip over a ferroelectric surface can trigger changes, varying from the removal of surface adsorbates and chemical doping of the near surface layer at low contact force, 43 to mechanically induced polarization switching when significant contact forces are exerted via strain gradient effects. [44][45][46] AP-XPS, in contrast, is sensitive to the chemical species and reactions occurring at the ferroelectric surface under water exposure, although at admittedly lower spatial resolution.…”
Section: Introductionmentioning
confidence: 99%